ANALISIS PENDAPATAN DAN PEMASARAN IKAN LELE DUMBO DI DESA MOJOMULYO KECAMATAN PUGER - Antika Fahriatul Fauziah; Titin Agustina; Yuli Hariyati (University of Jember, 2016)
Mojomulyo village Subdistrict of Puger one of the contres of catfish cultivation in Jember regency. In this prosess of growing up the catfish, the woof is the largest cost at all the process. The result of producing catfish should be in mutual accord with the marketing efficiency because the price of selling would give the impact to the cultivators income. This study aims to the income of catfish cultivator, the factor influencing the income catfish, and marketing of catfish in Mojomulyo village Subdistrict Puger. The research method is descriptive , analytical, and corelational method. The method of collecting the data used Proporsional Cluster Ramdom Sampling and Snowball Sampling . The results showed (1) The income of this business catfish cultivation is profitable; (2) The factors that signifantly the income of catfish cultivators are the cost of seed, the cost of woof, total production, the price of selling, the cost of labor, the cost of vitamins and another supplement; (3) The are 3 channels of marketing catfish. Based on value of marketing efficiency, the marketing channel of catfish is efficient. The 1st channel is the most efficient channel to profit share that received the highest cultivator fo 84,38% and distribution margin value, the 1st channel showed value of profit share and cost share more proportional.